Network know-how : an essential guide for the accidental admin - Ross, John, 1947- (No Starch Press, 2009)
"Network Know-How is your guide to connecting your machines, filled with practical advice that will show you how to get things done. You'll learn the nitty-gritty of network setup, design, and maintenance, from running cables and placing wireless access points to configuring file sharing and printing. This practical and comprehensive guide will teach you how to implement security, create intranets, and more."--Jacket.